Penggunaan Aplikasi Canva Untuk Meningkatkan Hasil Belajar Siswa Pada materi mengenali hewan Kelas 3 Sekolah Dasar - Sabillah Nurviana; Ibnu Muthi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Science learning is a boring lesson for students in some schools. There are several factors that cause students’ boredom in learning, one of the factors is because teachers at these schools are only fixated on books, so students become bored and this has an impact on their learning outcomes. The aim of this research is to develop science learning media using the Canva application to improve elementary school students’ learning outcomes. The method used in this research uses a systematic literature review where the results of the research are articles related to Canva learning media and active learning for elementary schools published between 2021-2024. Based on the results of this research, it can be concluded that the use of the Canva application is very effective in improving elementary school students’ learning outcomes.